Comparison of the Background Radiation Level within Kanchanpur District, Nepal - Dhami, G. B.; Bhatt, M. R.; Khadayat, J.; Joshi, B. D. (Journal of Nepal Physical Society, 2020)
We have reported the background radiation of urban and some other rural places of Kanchanpur district, Nepal. A simple portable Geiger Muller counter was used to quantify the level of overall background radiation by collecting data of different forty seven (including six urban and forty one rural places) places within the district. Our study reveals that the background radiation level of the study district is below the risk level. The maximum background count values 33.00±4.47 (Mahakali Zonal Hospital), 33.93 ± 1.16 (Mahakali School, Mahakali -01) and 31.30±3.97 CPM (Gha gaon) have been reported which is below the risk level. The observed values of radiation counts at all the sample places indicate that Kanchanpur district is radiation risk free.